The role of structural factors in real interest rate behaviour: A cross-country study - Ariefianto, Moch. Doddy; Trinugroho, Irwan (UNIVERSITY OF MERDEKA MALANG, 2020)
Real Interest Rate (RIR) has a profound impact on the well-functioning of any economy hence a good understanding of its behavior is a key policy element. Using a Keynesian framework, we model and empirically test the relationship of RIR to selected structural variables namely inequality, dependency, financial depth, and institutional set up. We employ a panel dataset comprised of 115 countries with annual frequency from the period 2000 to 2018. Considering the structure of the dataset and possible endogeneity in the model; System GMM is used to estimate regressions parameters. We found that inequality and dependency do not have a significant influence on RIR. Financial development contributes to improving efficiency while institutional set up has a quadratic relationship with RIR. The better institution first increases RIR; after passing a certain cut off; further institution development would improve efficiency. RIR is found to be significantly procyclical. Further elaboration on the model; also revealed two different global RIR regimes with 2008 as threshold. There is also a significant counter cycle impact of financial development: negative interaction effect with the business cycle. JEL Classification: C23, E43, E32, O43 DOI:Â https://doi.org/10.26905/jkdp.v24i3.4777